2009
DOI: 10.1007/s11666-009-9427-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spray Materials and Their Surface Oxidation on the Critical Velocity in Cold Spraying

Abstract: The critical velocity is an important parameter in cold spraying, which determines the deposition efficiency under a given spray condition. The critical velocity depends not only on materials types, but also on particle temperature and oxidation conditions. In the present paper, three types of materials including copper, 316L stainless steel, Monel alloy were used to deposit coatings by cold spraying. The critical velocities of spray materials were determined using a novel measurement method. The oxygen conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…If the velocities of the particles are higher than critical velocity, there will be strong erosion as a result of hydrodynamic penetration. The optimum velocity for efficient deposition and good quality bonding lies between these two velocities [18]. The optimum velocity obtained from the statistical calculation is in good agreement with the value obtained from the CFD at temperature of 500˝C (773 K).…”
Section: Exit Velocitysupporting
confidence: 77%
See 1 more Smart Citation
“…If the velocities of the particles are higher than critical velocity, there will be strong erosion as a result of hydrodynamic penetration. The optimum velocity for efficient deposition and good quality bonding lies between these two velocities [18]. The optimum velocity obtained from the statistical calculation is in good agreement with the value obtained from the CFD at temperature of 500˝C (773 K).…”
Section: Exit Velocitysupporting
confidence: 77%
“…Basically, the velocity of the particle is always less than that of the carrier gas. Therefore, the velocity of the carrier gas must be substantially above the critical velocity for deposition of high quality coating [18]. Li et al [33] reported that particle temperature affects critical velocity.…”
Section: Thermo-physical Properties and Boundary Conditionsmentioning
confidence: 99%
“…Limited research has been performed on 316L stainless steel coatings using cold spray (Ref [18][19][20][21][22][23][24]. The formation of recrystallized, nanoscale grains near particle interfaces in the as-sprayed 316L coating (N 2 and He-sprayed) was observed through TEM analysis (Ref 18) while EBSD analysis revealed a fully recrystallized microstructure after annealing (compressed air-sprayed coatings) (Ref 23).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of Cu particle velocity (measured in situ during the coating process) on deposition efficiency and bonding has been evaluated ( Ref 9,12,16). The DeLaval nozzle design has also been optimized on the basis of maximizing the particle velocity for a given input conditions ( Ref 17).…”
Section: Introductionmentioning
confidence: 99%